Identifying factors to boost species discoveries among reptile museum specimens - Guedes, Jhonny José Magalhães (2019)
Most species on Earth remain unknown to science and might go extinct before we ever recognize their existence. Specimens belonging to many of those missing species may have been already collected and housed in scientific collections, although they can remain “shelved” for years without a formal name. We investigate the time lag between collection and description dates of recently described species, and its determinants. We reviewed the literature on species descriptions of global reptile species from 1992 to 2017, gathering data on biological and sociological variables for 2,661 species. We used time-to-event analysis in concert with a model averaging approach to investigate what factors contribute to explain variation in time lag. The time lag of global reptiles varied from zero to 155 years (median = 5 years). More than one-quarter of the descriptions involved specimens shelved for 12 years or more. Time lags were shorter when the collector of the holotype was an author of description, and taxonomic revisions uncovered species with longer time lags. Unknown species eventually collected by citizen scientists may therefore remain shelved for much longer in scientific collections. Taxonomic revisionary studies are crucial to reverse this trend and improve the benefits from citizen science. Our findings reveal which kind of preserved reptile specimens can likely represent yet unknown species in scientific collections. Keywords: Species discoveries. Biodiversity conservation. Linnaean shortfall. Taxonomic impediment. Shelf life. Preserved specimens. Time lag.